The Influence of Personality and Work Motivation on Employee Performance Through the Mediating Role of Organizational Commitment (A Study at the Environmental Agency of Semarang City) - Tyas Astuti; Tristiana Rijanti (Journal Research of Social Science, Economics, and Management, 2025)
This research is motivated by the achievement of the performance of the Semarang City Environment Agency (DLH) in the 2021–2023 period, which has not met the targets in various main indicators, allegedly due to human resource factors such as personality, work motivation, and organizational commitment. This research aims to analyze the influence of personality and work motivation on employee performance, both directly and indirectly through the mediating role of organizational commitment. The population used in this study consists of all Civil Servants (PNS) who work at the Semarang City Environment Agency with criteria including permanent employees and a minimum working period of three years. The total population is 80 people, and the sampling technique used is the census method or saturated sample, resulting in 80 respondents. The data source used was primary data, collected through a questionnaire. The data analysis technique employed was path analysis using the SPSS version 25 program. The results of the study show that personality variables have a positive and significant effect on organizational commitment, and work motivation has a positive and significant effect on organizational commitment. Personality has a positive and significant effect on employee performance, work motivation has a positive and significant effect on employee performance, and organizational commitment has a positive and significant effect on employee performance. The results of the mediation test showed that organizational commitment can mediate the influence of personality and work motivation on employee performance.